Upgrading a linear controller to a sliding mode one: Theory and experiments. (June 2022) - Perozzi, Gabriele; Polyakov, Andrey; Miranda-Villatoro, Félix; Brogliato, Bernard
Abstract: This article proposes a procedure for upgrading a linear proportional controller to a sliding mode one preventing a degradation of a control quality. Two nonlinear algorithms are studied in this context: Unit and Homogeneous Sliding Mode Controllers (SMCs). The parameters of the nonlinear controllers are defined using the gains of the (already well-tuned) linear controller. The main idea of this upgrading procedure is to split the state-space into two regions, the region of the linear control and the region of the nonlinear control. This is done via a suitable design parameter. The theoretical developments are validated experimentally on a rotary inverted pendulum. Comparisons between the already well-tuned linear controller and the proposed upgraded nonlinear controllers are presented. The experiments in a rotary inverted pendulum demonstrate that the upgraded controller significantly improves the control precision without degradation of the control signal.